Perception Student to School Teacher Education Study Program Services Base - Ahadin, Ahadin; Alam, Faisal; Sapriya, Sapriya; Perdana, Rifandi; Iqbal, Rahmat (Soedirman Economics Education Journal, 2024)
This research aims to determine students' perceptions of Bina Bangsa Getsempena University's PGSD study program services in terms of tangibles, reliability, responsiveness, certainty and empathy in order to serve as an illustration or guideline for Bina Bangsa Getsempena University's PGSD study program services. more Good Again in the future. Method in study This that is descriptive with approach quantitative. Study This done with spread questionnaire via google form to student. Sample in study This as many as 22 students. Types of research data This namely primary data and sources the data Bina Bangsa University PGSD study program student Getsempena Class of 2022 which was created sample. Research instruments used _ is questionnaire use scale likert that uses alternative answers Very Good ( SB), Good (B), Neutral (N), No Good (TB), Very no good (STB). Research results This show that perception to service academic categorized as Good with percentage 86.72% And service administration categorized as Good with percentage 84.8% So can is known that perception student towards the Bina Bangsa University PGSD study program Gethsempena categorized as with Good with an average percentage of 85.76%